Diagnosis and treatment of dyslipidemias - Stalenhoef, Anton (Henry Stewart Talks, 2008)
Primary dyslipidemias, Autosomal dominant and recessive hypercholesterolemia, Familial hypercholesterolemia, Familial combined hyperlipidemia, Familial hypertriglyceridemia, Familial dysbetalipoproteinemia, Pharmacotherapy, Secondary dyslipidemias